Design and Characterization of Y2O3/Pr2O3-Enriched Inconel-718 Alloys for Nuclear Applications - Albayrak, Muhammet Gokhan; Guler, Omer; Guler, Seval Hale; Evin, Ertan; Almisned, Ghada; Sen Baykal, Duygu; Tekin, Huseyin Ozan (Taylor & Francis Inc, 2026)
This study explores the physical, structural, and radiation shielding enhancements in Inconel 718 superalloys reinforced with 1 wt% Y2O3 and varying Pr2O3 contents from 0 to 10 wt%, respectively. X-ray diffraction analysis confirmed preservation of the face-centered cubic structure, with increasing Pr2O3 inducing peak broadening and partial amorphization. The scanning electron microscopy/energy-dispersive X-ray spectroscopy results verified the homogeneous dispersion of oxides without agglomeration. Gamma-ray shielding parameters, including the mass attenuation coefficient (MAC), half-value layer, and effective atomic number, significantly improved with higher Pr2O3 content, particularly at low to mid photon energies.The 718Y-10PO sample exhibited the lowest transmission factors and the highest MAC values across all the tested energies. Buildup factors decreased in the Pr-rich samples, confirming reduced photon scattering. Notably, the fast neutron removal cross section for 718Y-10PO as 0.15521 cm-1 exceeded the benchmark materials like graphite and B4C. These findings establish the 718Y-10PO alloy as a promising candidate for advanced nuclear shielding applications, combining structural integrity with promising gamma and neutron attenuation capabilities.
Keywords: Nickel-based superalloys; rare earth oxide reinforcement; gamma-ray attenuation; fast neutron shielding; praseodymium oxide